Pengembangan Model Navigasi Nilai Sosial untuk Mendukung Kerangka Kerja Pengembangan Strategi Organisasi Sosial di Dalam Choeling Indonesia - Ledy, Ledy; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2013)
Every social organization has a unique different business model in providing services to the society. The social business model is often derived from a selected strategy. However, the strategy merely directs the social business model to construct its elements by neglecting value related aspects. There is no formal social business model concept that assists any strategy framework used as the basic structure for identifying a business model, especially the value concerned business model. The aim of this research is thus to construct a Social Value Navigation Model to complement a strategy development framework based on the Business Model Canvas and Blue Ocean Strategy. The new model serves as a reliable strategy framework for a social organization to figure out the value aspects of Business Model Canvas and to modify them to fit the social sector. This social value navigation model has been applied at a religious organization and has resulted in appropriate solutions to overcome the weaknesses of the religious organizationâ€™s social business model.Â Keywords: social organization, business model, Social Value Navigation Model, Business Model Canvas, Blue Ocean Strategy